x - 2y = 6.............(1)

x + 2y = 8............(2)

We will solve using the elimination method.

We will add (1) + (2).

==> 2x = 14

Now we will divide bu 2.

==> x = 7

Now we will substitute into (1) to determine y.

==> x - 2y...

## See

This Answer NowStart your **subscription** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

x - 2y = 6.............(1)

x + 2y = 8............(2)

We will solve using the elimination method.

We will add (1) + (2).

==> 2x = 14

Now we will divide bu 2.

==> x = 7

Now we will substitute into (1) to determine y.

==> x - 2y = 6

===> 7 - 2y = 6

==> -2y = -1

==> y= 1/2

**Then the answer is the pair ( 7, 1/2)**

We have to solve the following set of simultaneous equations:

x - 2y = 6 ...(1)

x + 2y = 8 ...(2)

(2) - (1)

=> x + 2y - x + 2y = 8 - 6

=> 4y = 2

=> y = 2/4

=> y = 1/2

substitute in (1)

x - 2y = 6

=> x = 6 + 2y

=> x = 6 + 2*(1/2)

=> x = 6 + 1

=> x = 7

**We get x = 7 and y = 1/2**